Rhabdosoma whitei Spence Bate 1862 - Gasca, Rebeca; Hendrickx, Michel E. (Zenodo, 2022)
Rhabdosoma whitei Spence Bate, 1862 Rhabdosoma whitei Spence Bate, 1862: 345‒346, pl. LIV, fig. 7; Brusca, 1981: 12 (list), 32 (key), fig. 2c; Siegel-Causey, 1982: 350 (key), 353‒354; Vinogradov et al ., 1996: 536 (key), 538-540, fig. 232; García Madrigal, 2007: 158 (list); Guillén Pozo, 2007: 17 (key), 109‒110, fig. 38; Gasca, 2009: 89 (tab. 1); Lavaniegos & Hereu, 2009: 142 (tab. 1),152 (appendix); Gasca et al ., 2012: 126 (tab. 1), 133 (tab. 4); Valencia & Giraldo, 2012: 1493 (tab. 1); Lavaniegos, 2014: 3, 5 (tab. 1); 2017: 21; Valencia et al ., 2013: 52 (tab. 1); Zeidler, 2016: 79 (passim), fig. 36B, 36A2, 80 (key); Violante-Huerta et al ., 2021: 81 (tab. 1), 86, fig. 2E. Material examined . 45M, 76F, in 20 localities (Fig. 4). TALUD III. St. 3B (22°36’36”N, 106°35’54”W), August 17, 1991, 2F, I-K from surface to 275 m (TD, 1585 m) (ICML-EMU-12968-A); St. 5 (23°22’N, 107°10’W), August 24, 1991, 1F, I-K, from surface to 365 m (TD, 698 m) (ICML-EMU-12968-B); St. 10B (23°43’24”N, 107°39’06”W), August 18, 1991, 2M, 1F, I-K from surface to 630 m (TD, ca. 900 m) (ICML-EMU-12968-C); St. 19 (25°12’00”N, 109°07’00”W), August 20, 1991, 1M, 2F, I-K, surface to 410 m (TD, 920 m) (ECOSUR-10561); St. 19B (25°18’24”N, 109°18’36”W), August 20, 1991, 3M, 4F, I-K from surface to 600 m (TD, 1890 m) (ICML-EMU-12969-A); St. 25A1 (25°51’00”N, 109°57’00”W), August 21, 1991, 1M, 1F, I-K from surface to 200 m (TD, 1280‒1360 m) (ICML-EMU-12969-B); St. 25A2 (25°50’54”N, 109°56’54”W), August 21, 1991, 2M, 1F, I-K from surface to 230 m (TD, ca. 1200 m) (ICML-EMU-12969-C). TALUD IV St. 7 (22°00’22”N, 106°49’18”W), August 23, 2000, 2M, 4F, MN from surface to 500 m (TD, 1970 m) (ICML-EMU-12970-A); St. 15 (23°23’30”N, 107°47’48”W), August 24, 2000, 3F, MN from surface to 1500 m (TD, 2350 m) (ICML-EMU-12970-B; St. 22 (24°17’20”N, 108°50’30”W), August 26, 2000, 1M, 3F, MN from surface to 1325 m (TD, aprox. 1800 m) (ICML-EMU-12971-A); St. 29 (24°57’48”N, 109°37’00”W), August 27, 2000, 1M, MN from surface to 1280 m (TD, 2080 m) (ICML-EMU-12971-B). TALUD V. St. 5 (22°00’57”N, 106°40’00”W), December 13, 2000, 1M, 1F, MN from surface to 1400 m (TD> 1600 m) (ICML-EMU-12972-A); St. 29 (25°14’36”N, 109°24’15”W), December 17, 2000, 1F, MN from surface to 1290 m (TD, 2040 m) (ICML-EMU- 12972-B); St. 36. (25°54’30”N, 110°11’24”W), December 17, 2000, 1M, 2F, MN from surface to 1340 m (TD, 1990 m) (ICML-EMU-12972-C). TALUD VI. St. 7 (22°21’39”N, 107°01’42”W), March 14, 2001, 23M, 45F, MN from surface to 1305 m (TD, 2100 m) (ICML-EMU-12973-A); St. 15 (23°14’42”N, 107°30’00”W), March 14, 2001, 3M, 2F, MN from surface to 1230 m (TD, 2390 m) (ICML-EMU-12973-B); St. 22 (24°17’34”N, 108°50’25”W), March 15, 2001, 1M, 2F, MN from surface to 1410 m (TD, 1760 m) (ICML-EMU-12973-C). TALUD VII. St. 22 (24°21’08”N, 108°55°14” W), June 7, 2001, 1M, MN from surface to 1415 m (TD, 2000 m) (ICML-EMU- 12974). TALUD IX, St. 7 (25°11’30”N, 109°41’06”W), November 15, 2005, 1M, MN, surface to 1510 m (TD, 2377 m) (ICML-EMU-12975-A). TALUD X, St. 11 (27°34’16”N, 111°40’W), February 11, 2007, 1M, MN, from surface to 1215 m (TD, 1801 m) (ICML-EMU-12975-B). TALUD XI. St. 19B (17°56’00”N, 103°10’00”W), June 9, 2007, 1F, MN from surface to 1200 m (TD, 1995 m) (ICML-EMU-12976-A). TALUD XII. St. 28B (18°56’00”N, 104°59’57”W), April 2, 2008, 1M, MN from surface to 1425 m (TD, 2041 m) (ICML-EMU-12976-B). Distribution . Tropical and subtropical in the Pacific, Atlantic, and Indian Oceans, from 40°N to 40°S. Mediterranean and Red Seas. In the eastern Pacific from Mexico to Costa Rica, Panama, Colombia, and Ecuador (Vinogradov et al . 1996, García Madrigal 2007, Valencia & Giraldo 2012, Valencia et al . 2013, Violante-Huerta et al . 2021, this study). Remarks . One specimen (ICML-EMU-12975-A)was attached to the siphonophore Diphyes bojani (Eschscholtz, 1825); although it looked like a natural union, this could be a consequence of the sampling method. Rhabdosoma whitei has been observed previously associated with the ctenophore Beroe sp. (Harbison et al . 1978). Mostly from surface to 200 m depth (Vinogradov et al . 1986). An epipelagic species reported as relatively common in the entire Gulf of California (Siegel-Causey 1982). In the Mexican part of the California Current Rhabdosoma whitei has been consistently reported by Lavaniegos & Hereu (2009) and by Lavaniegos (2014, 2017), but not as a dominant species (present in 12% of the samples; Lavaniegos 2014). Our data indicate that R. whitei is a frequent species throughout the Gulf of California, also recorded off SW Mexico (Fig. 4). : Published as part of Gasca, Rebeca & Hendrickx, Michel E., 2022, Pelagic amphipods (Crustacea: Amphipoda: Hyperiidea) in western Mexico. 7 Superfamily Platysceloidea. Family Oxycephalidae, pp. 219-236 in Zootaxa 5105 (2) on pages 227-229, DOI: 10.11646/zootaxa.5105.2.3, http://zenodo.org/record/6332529 : {"references": ["Spence Bate, C. (1862) Catalogue of the Specimens of Amphipodous Crustacea in the Collection of the British Museum. British Museum Natural History, London, i - iv + 1 - 399, pls. 1 - 56.", "Brusca, G. J. (1981) Annotated keys to the Hyperiidea (Crustacea: Amphipoda) of North American coastal waters. Allan Hancock Foundation Technical Reports, 5, 1 - 76. https: // doi. org / 10.2307 / 1547968", "Siegel-Causey, D. (1982) Factors determining the distribution of hyperiid Amphipoda in the Gulf of California. Ph. D. Thesis, University of Arizona, Tucson, Arizona, 535 pp.", "Vinogradov, M. E., Volkov, A. F. & Semenova, T. N. (1996) Hyperiid amphipods (Amphipoda, Hyperiidea) of the world oceans. Oxonian Press Pvt. Ltd., New Delhi, 632 pp.", "Guillen Pozo, W. (2007) Composicion y distribucion de Amphipoda (Hyperiidae) en aguas ecuatorianas durante el evento de La Nina 2005. Graduate Thesis, Facultad de Ciencias Naturales, University of Guayaquil, Guayaquil, Guayas Province, 218 pp.", "Lavaniegos, B. E. & Hereu, C. (2009) Seasonal variation in hyperiid amphipod abundance and diversity and influence of mesoscale structures off Baja California. Marine Ecology Progress Series, 394, 137 - 152. https: // doi. org / 10.3354 / meps 08285", "Gasca, R., Franco-Gordo, C., Godinez-Dominguez, E. & Suarez-Morales, E. (2012) Hyperiid amphipod community in the Eastern Tropical Pacific before, during, and after El Nino 1997 - 1998. Marine Ecology Progress Series, 455, 123 - 139 https: // doi. org / 10.3354 / meps 09571", "Valencia, B. & Giraldo, A. (2012) Structure of hyperiid amphipod assemblages on Isla Gorgona, eastern tropical Pacific off Colombia. Journal of the Marine Biological Association of the United Kingdom, 92 (7), 1489 - 1499. https: // doi. org / 10.1017 / S 0025315411001780", "Lavaniegos, B. E. (2014) Pelagic amphipod assemblage associated with subarctic water off the West Coast of the Baja California Peninsula. Journal of Marine Systems, 132, 1 - 12. https: // doi. org / 10.1016 / j. jmarsys. 2013.12.012", "Valencia, B., Lavaniegos, B., Giraldo, A. & Rodriguez-Rubio, E. (2013) Temporal and spatial variation of hyperiid amphipod assemblages in response to hydrographic processes in the Panama Bight, eastern tropical Pacific. Deep-Sea Reseach I, 73, 46 - 61. https: // doi. org / 10.1016 / j. dsr. 2012.11.009", "Zeidler, W. (2016) A review of the families and genera of the superfamily Platysceloidea Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. Zootaxa, 4192 (1), 1 - 136. https: // doi. org / 10.11646 / zootaxa. 4192.1.1", "Violante-Huerta, M., Morales-Ramirez, A. & Sanvicente-Anorve, L. (2021) Anfipodos pelagicos (Amphilochidea, Hyperiidea y Senticaudata) del Pacifico de Costa Rica: nuevos registros y una lista de especies actualizada. Revista de Ciencias Marinas y Costeras, 13 (1), 77 - 97. https: // doi. org / 10.15359 / revmar. 13 - 1.5", "Harbison, G. R., Madin, L. P. & Swanberg, N. R. (1978) On the natural history and distribution of oceanic ctenophores. Deep-Sea Research, 25, 233 - 256. https: // doi. org / 10.1016 / 0146 - 6291 (78) 90590 - 8", "Lavaniegos, B. E. (2017) Changes in composition of summer hyperiid amphipods from a subtropical region of the California Current during 2002 - 2008. Journal of Marine Systems, 165, 13 - 26 https: // doi. org / 10.1016 / j. jmarsys. 2016.09.001"]}